Association of the IL-6 -174G > C (rs1800795) Polymorphism with Adolescent Idiopathic Scoliosis: Evidence from a Case-Control Study and Meta-Analysis - Sobhan, Mohammad Reza (Rev Bras Ortop (Sao Paulo), 2020)
Recent epidemiological studies have identified that the -174G > C (rs1800795) polymorphism in the promoter region of the interleukin-6 ( IL-6 ) gene is associated with the risk of developing adolescent idiopathic scoliosis (AIS), but they presented inconsistent and controversial results. Thus, we performed a case-control study and meta-analysis to derive a more precise estimation of the relationship between the IL-6 -174G > C polymorphism and the risk of developing AIS. A total of 80 patients with AIS and 80 matched healthy control subjects were genotyped using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) assay. In addition, all eligible studies published up to June 2018 were identified through a search in the PubMed, EMBASE, Google Scholar, and China National Knowledge Infrastructure (CNKI) databases. We calculated the odds ratios (ORs) and 95% confidence intervals (95%CIs) to assess the association. A total of 10 eligible studies comprising 1,695 AIS cases and 2,097 healthy controls were included in the meta-analysis. The pooled data suggested a significant association between the IL-6 -174G > C polymorphism and the susceptibility to develop AIS, which was demonstrated under 4 genetic models, that is, the allelic (C versus G; OR = 0.671; 95%CI: 0.457–0.985; p  = 0.042), heterozygous (CG versus GG; OR = 0.734; 95%CI: 0.554–0.973; p  = 0.032), dominant (CC + CG versus GG; OR = 0.660; 95%CI: 0.440–0.990; p  = 0.044) and recessive models (CC versus CG + GG; OR = 0.506; 95%CI: 0.264–0.970; p  = 0.040). The stratification analysis by ethnicity revealed an increased risk of developing AIS in Caucasians, but not in Asians. The present meta-analysis, which is inconsistent with the previous meta-analysis, suggests that the IL-6 -174G > C polymorphism may increase the individual susceptibility to develop AIS, especially in Caucasians, and it could serve as a biomarker to predict the population at high risk of developing AIS.